The Effect of Observational Learning towards Students' Writing Skill - Nugroho, Ifnu; Mulyana, Agus; Nuraini, Hery (Foremost Journal, 2022)
The aim of this research was to know the effect of students' writing skill through Observational Learning in SMKI Al-Khoirat Kabupaten Tangerang. This research is quantitative method, 30 students as the sample which taken not random by using Quasi-Experimental as the research. This design will performed using only one group without a control group. Students' test were used by the researcher to collect the data. The hypotheses data was tested using formula of Wilcoxon, it was known the output 'test statistic' Asymp. Sig. (2-tailed) = 0,000 < 0,05. Because the value of 0,000 is less than 0,05, It means, there is a significance differences between pre-test and post-test in experimental class using Observational Learning at the tenth grade of SMKI AL-KHOIRAT Kabupaten Tangerang, because before giving a treatment, the students lack knowledge in narrative text. Then, it was also known from the percentages students' post-test showing 79% students can pass writing skill, although many students cannot pass the KKM. Moreover students can improve their narrative writing skill after using observational learning method.